Physicochemical Characterization of Kahata Angala (Dioscorea alata) Starch and its Potential as a Binder in Losartan Potassium Tablet Formulation - Samarasinghe Arachchillage Nuwani Chathurika Samarasınghe; Sriaandhal Sabalingam; Banneka Mudiyansele Walawwe Ishara Methsalani Warapitiya; Samamalee Upekshi Kankanamge; Ranjith Nandalal Pathirana (Journal of Food Innovation, Nutrition, and Environmental Sciences)
This study focused on developing a pharmaceutical-grade starch as a natural binder from yam species. The starch was isolated from the yam rhizome of Kahata Angala (Dioscorea alata) which is widely found in Sri Lanka. The physicochemical parameters and morphology of the starch were analyzed and compared with maize starch BP. The isolated yam starch was used as a binder to formulate losartan potassium tablets using the wet granulation method with a 10% w/v starch binding solution. Losartan potassium tablets were further assessed for some critical parameters, including weight variation, friability, hardness, thickness, dissolution, and disintegration. The findings indicated that compared to maize starch BP, Kahata Angala starch has greater flow characteristics, suggesting lesser values for compressibility index (22.20 ± 1.39), angle of repose (38.02 ± 0.60º) and Hausner ratio (1.29 ± 0.02) than maize starch BP. Tablets formulated with Kahata Angala starch exhibited a good friability percentage, which was less than 1%. Based on the outcomes, it can be concluded that certain parameters of starch obtained from Kahata Angala is more suitable than maize starch BP. However, further optimization is needed for the disintegration and dissolution profiles.